Perlindungan Hukum Pemegang Hak atas Sertifikat dalam Kendala Pendaftaran Tanah Sistematis Lengkap di Kantor Pertanahan Jakarta Timur - Eka Noviani Kusumastuti; Fitra Deni (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Problem: The Complete Systematic Land Registration aims to facilitate and benefit economically disadvantaged communities. However, in its implementation, many Land Deed Officials become victims due to dishonesty in deed making, especially in the East Jakarta area. Purpose: This research aims to examine the legal consequences of certificate management through Complete Systematic Land Registration at the East Jakarta Land Office and the legal protection for rights holders concerning the validity of the resulting certificates. Methodolgy: This research uses a normative empirical approach. The data used consists of primary and secondary data obtained from literature materials and field data through interviews. The theories applied in this research are the Legal Protection Theory and the Legal Certainty Theory. This research finds that legal protection for land certificate holders through Complete Systematic Land Registration provides legal certainty guarantees as the certificate functions as an identification and court documentation. As long as no other party can prove otherwise, the land certificate is considered valid, and the listed owner is recognized as the rightful owner. Results/Findings: Legal protection for rights holders regarding the validity of certificates at the East Jakarta Land Office includes two types: preventive and repressive. Preventive protection aims to prevent problems from arising, while repressive protection focuses on dispute resolution. The analysis results indicate that although PTSL brings significant benefits, oversight and honesty in deed-making are crucial to avoid legal issues in the future